Factors influencing Generation Y towards purchase intention on green products / Nur Amirah Merazman - Merazman, Nur Amirah (2015)
This research was conducted to carry out a study entitled “Factors Influencing Generation Y Towards Purchase Intention on Green Products”. The purpose of this study is to investigate the relationship between four independent variables against one dependent variable, to identify which factor is most important towards purchase intention on green products and to provide recommendation to improve the purchase intention of green products. Basically, it consists of four factors influencing purchase intention on green products in Generation Y in Universiti Teknologi MARA Kampus Bandaraya Melaka and the factors are perceived consumer effectiveness, health consciousness, environmental concern and social influence. In order to complete this write up, a few hypotheses were constructed. For this study, 335 students in Universiti Teknologi MARA Kampus Bandaraya Melaka were chosen as respondents for this study. However, only 200 responses were returned back to the researcher. The data was obtained from primary data by using questionnaires. All data collected through the questionnaires were analysed systematically by Statistical Package for Social Science (SPSS). From the correlation testing, the result shows four independent variables has relationship with dependent variable. In terms of hypotheses results, all the hypothesis are accepted. For multiple regression analysis, the most important factor is environmental concern.